Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
x= -1/3
x = -7
Step-by-step explanation:
9x^2 +66x+21 = 0
a=9 b=66 c=21
quadratic formula
x=(-b +/- square root of (b^2 – 4ac))/(2a)
x = (-66 +/- square root of (66^2 -4*9*21))/(2*9)
x = (-66 +/- square root of (4356 -756))/(18)
x = (-66 +/- square root of (3600))/(18)
x = (-66 +/- 60)/18
split the fraction
(-66 +/- 60)/18 = -6/18 and -126/18 because of the +/-
x = -6/18 x = -126/18
x = -1/3 x = -7
[tex]~~~~~~9x^2+66x+21 = 0\\\\\implies 3(3x^2+22x+7)=0\\\\\implies 3x^2+22x+7=0\\\\\implies 3x^2 +21x +x +7=0\\\\\implies 3x(x+7) +(x+7)=0\\\\\implies (x+7)(3x+1)=0\\\\\implies x = -7~~ \text{or}~~ x =-\dfrac 13[/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.